Etiopathological Study of 50 Patients of Cutaneous Lichen Planus in Ayurveda - Jejulee Narzary; Anup Baishya; Ramakanta Sharma; Pankaj Kr. Barman (AYUSHDHARA, 2022)
Lichen planus is a distinctive dermatosis characterized by pruritic violaceous flat topped papule or plaque with a network of white lines called the Wickham’s striae. First introduced by Erasmus Wilson in 1869, it an idiopathic inflammatory, autoimmune disorder affecting the skin, the mucous membrane, hairs and nails. Sites involved in skin are the flexor surface of wrists and forearms, dorsal surface of hands, anterior aspect of lower legs, neck and pre sacral area. In Ayurveda, though there is no direct reference of cutaneous lichen planus like diseases, there are certain skin lesions mentioned under Kusthas like Charmakustha, Kitibha Kustha, Vicarchika and Alasa having signs and symptoms similar to cutaneous lichen planus. An attempt has been made to study the aetiopathogenesis of cutaneous lichen planus in Ayurveda and to evaluate the common Nidanas mentioned under Kustha, which are commonly responsible for causation of the disease. For this purpose, a study was done on 50 patients suffering from cutaneous lichen planus. The patients were selected randomly from OPD & IPD; Govt. Ayurvedic College and Hospital, Guwahati, Assam. Proper history was taken in a specially designed proforma to evaluate the most common Nidanas. From this study it was found that there is a definite role of Aharaja, Viharaja and Manasik Nidanas in cutaneous Lichen planus. The Nidanas were mostly Pitta-Kapha Vardhak Ahar-Viharas like Gramya Anupa Udaka Mamsa, Ati Lavana Sevana, Diwaswapna, Vegdharana, etc. This study can be beneficial in preventing the occurrence and recurrence of lichen planus on adopting Nidana Parivarjanam.